2016
DOI: 10.1002/2016gl070154
|View full text |Cite
|
Sign up to set email alerts
|

Ground detection of terrestrial gamma ray flashes from distant radio signals

Abstract: Terrestrial gamma ray flashes (TGFs) are brief bursts of energetic gammy‐ray photons generated during thunderstorms, which have been detected almost exclusively by satellite‐based instruments. Here we present three lines of evidence which includes the three out of three simultaneously observed pairs, the same occurrence contexts, and the consistent estimated occurrence rate, which indicate a direct relationship between a subset of TGFs and a class of energetic radio signal easily detectable by ground‐based sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 30 publications
6
98
0
2
Order By: Relevance
“…From this expectation, the present high‐current discharges are probably only ones the detectors experienced in the 2017–2018 winter season. Based on the fact that each detector observed only one downward TGF in the 2017–2018 season, we speculate that such high‐current discharges could have a strong connection to downward TGFs, as Lyu et al () proposed for positive EIPs and upward TGFs. Namely, all EIPs might be associated with downward TGFs.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…From this expectation, the present high‐current discharges are probably only ones the detectors experienced in the 2017–2018 winter season. Based on the fact that each detector observed only one downward TGF in the 2017–2018 season, we speculate that such high‐current discharges could have a strong connection to downward TGFs, as Lyu et al () proposed for positive EIPs and upward TGFs. Namely, all EIPs might be associated with downward TGFs.…”
Section: Discussionmentioning
confidence: 58%
“…Recent observations in the RF band have identified a new class of in‐cloud discharge currents associated with TGFs, called “energetic in‐cloud pulses” (EIPs; Lyu et al, , ; Lyu & Cummer, ). EIPs have high peak currents of >100 kA and are distinguished from other lightning classes such as return strokes (RSs) of cloud‐to‐ground discharges and narrow bipolar events (NBE; Rison et al, ) by characteristics of RF waveforms (Lyu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by these observations, as well as by recent efforts to understand [3,4,5,6,7,8] the Terrestrial Gamma Flashes (TGFs) observed by satellite-borne detectors [9,10], a suite of lightning mapping (LMA) and electric field-measuring instruments were deployed at the Telescope Array detector site in Western Utah, U.S.A. Here, we report on the first joint observations with the TA/LMA instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Once identified with sprites, they are now widely believed to originate in upward-propagating negative leaders in intracloud lightning flashes [3][4][5][6][7][8]. Given this interpretation, it is natural to ask whether downward propagating negative leaders might also produce gamma showers associated with cloud-to-ground lightning strikes.…”
Section: Introductionmentioning
confidence: 99%